Distribution of Al atoms in the clathrate-I phase Ba8AlxSi46−x at x = 6.912. Issue 28 (28th July 2015) - Bobnar, Matej; Böhme, Bodo; Wedel, Michael; Burkhardt, Ulrich; Ormeci, Alim; Prots, Yurii; Drathen, Christina; Liang, Ying; Nguyen, Hong Duong; Baitinger, Michael; Grin, Yuri
<x xml:space="preserve">Abstract</x> The distribution of Al and Si atoms in Ba8Al6.9Si39.1 was elucidated by combining the results of NMR, X-ray diffraction and chemical analysis.